Pengembangan E-LKPD Berbasis Question Prompt Scaffolding untuk Meningkatkan Berpikir Kritis Siswa SMP pada Pembelajaran IPA - Anggita Wahyuni Rohma; Aris Singgih Budiarso; Supeno Supeno (Universitas Pendidikan Mandalika, 2023)
The research aims to analyze the validity, practicality, and effectiveness of question prompt scaffolding-based E-LKPD products in improving students' critical thinking skills in science learning. The research method was research and development with the Plomp development model, which has three stages: preliminary research, prototype stage, and assessment phase. The research subjects were 23 class VII students of SMPN 12 Jember. The data analysis technique used qualitative data and quantitative data. The research instruments were validation sheets, learning implementation sheets, student response questionnaires, and pretest and posttest questions. The results of the E-LKPD validation score based on the question prompt scaffolding obtained 79.13% with valid criteria. The practicality of the E-LKPD based on question prompt scaffolding obtained a score of 88.05% with very practical criteria. The effectiveness of the question prompt scaffolding-based E-LKPD obtained an N-gain score of 0.66 with moderate criteria, while student response questionnaire scores obtained an average of 83.33% with good criteria. The results showed that the question prompt scaffolding-based E-LKPD was valid, practical, and effective in improving students' critical thinking skills in science learning.